Analysis of acoustic performance in wall and floor systems in multifamily buildings - Felipe Alves Amâncio; Stefanie Almeida Campos; Alisson Rodrigues de Oliveira Dias; Maria Fabiola de Carvalho Rafael; Alexandre Araújo Bertini (Revista de Engenharia Civil IMED, 2019)
The performance’s standard NBR 15575 started to demand from builders the minimum standards of quality and performance, in order to attend the user’s requirements and to seek greater market competitiveness. Unlike thermal comfort, acoustic comfort often ends up having less prominence, even knowing the discomfort and problems caused by unwanted noise. Therefore, the present work has as objective to evaluate the acoustic performance of wall and floor systems in vertical buildings. For data collection, field trials were carried out in buildings in the city of Fortaleza as recommended by the performance standard ABNT NBR 15575: 2013. Were evaluated the airborne insulation in wall and floor systems and the impact noise insulation in floor systems. It was verified that of 7 analyzed buildings, 2 did not reach the minimum performance in at least one criterion and that the use of acoustic blanket improves acoustic performance, observing a close relation of the acoustic comfort with the thickness and material of core and coating used. It is observed that construction systems currently used attend only the minimum required by the standard, being necessary the study of new technologies for a better acoustic performance of constructed buildings.